Laboratory diagnosis of primary amoebic meningo-encephalitis and methods for the detection of limax amoebae in the environment - Cerva, L (Folia parasitologica, 1980)
Laboratory examination methods and processes recommended for the diagnosis of primary amoebic meningo-encephalitis and detection of Naegleria fowleri in the environment are summarized. The most simple methods suitable for diagnostic laboratories in the sphere of medical parasitology have been chosen.
Keywords: mozek; Humans; Meningoencephalitis; amébiáza; Amoeba; půda; lidé; zvířata; myši; parazitologie; Mice; Amebiasis; mozkomíšní mok; Brain; voda; Cerebrospinal Fluid; Water; Animals; Soil; meningoencefalitida; Parasitology